Maslahah Mursalah As The Istinbath of The Law of Ibn Taimiyah in Conditional Waqf - Darlius (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
Many cases of waqf occur in the community, where waqif provides conditions that are not in accordance with the object of the waqf object. If someone wants to donate enough with the intention of endowments only. The research method that I use is library research, which is the object of research regarding Ibn Taimiyah's opinion in conditional waqf. In the research method, the author uses analytical content. in this case Ibn Taimiyah's opinion about the conditional and istinbath of Ibn Taimiyah's law will be explained about reservations and its participation in waqf contracts. The author conducts research on conditional waqf in Ibn Taimiyah's perspective, finally, the author concludes that Ibn Taimiyah's opinion on conditional waqf is the inclusion of conditions on waqf must realize the meaning of taqarrub (self approach to God). if waqif requires for certain fields that have no merit, then the effort is a futile both in the world and the hereafter. In short, such conditions are deemed null and void, but the endowments remain valid. in applying the istinbath of law, Ibn Taimiyah applied maslahah mursalah as his legal approach. Maslahah mursalah is a benefit that is considered to bring benefits to humans and is not found basically in syara '.